General immunologic reactivity of patients with COVID-19 and its relation to gene polymorphism, severity of clinical course of the disease and combination with comorbidities - M.O. Sokolenko; L.P. Sydorchuk; L.S. Sokolenko; A.A. Sokolenko (Medičnì Perspektivi)
The aim of the study is to identify and evaluate the general immunological reactivity of patients with COVID-19 and its relationship with gene polymorphism, severity of the clinical course of the disease and combination with comorbidities. A cohort study was conducted involving 204 patients with COVID-19 diagnosed with community-acquired pneumonia of mild, moderate, and severe degrees who also had comorbidities: endocrinopathies (46 patients), cardiovascular diseases (82 patients), and comorbidities of the ENT organs, connective tissue, gastrointestinal tract, chronic kidney disease (CKD), which were grouped into the group "other comorbidities (76 patients). Among the patients there were 51.97% (106) women and 48.03% (98) men. The average age of patients was 55.93±8.75 years. The polymorphism of the NOS3 (rs2070744), FGB (rs1800790) and TMPRSS2 (rs12329760) genes was determined by real-time polymerase chain reaction (qualitative determination). The overall immunological reactivity was detected and evaluated based on the analysis of 14 integral leukocyte indices: leukocyte shift index, absolute leukocyte count/erythrocyte sedimentation rate (ESR) ratio index, lymphocyte-granulocyte index, lymphocyte index, immunological resistance and reactivity index, and others. The overall immunological reactivity of the body of patients with coronavirus infection increases in the presence of the wild-type T-allele of the eNOS gene (rs2070744) in the patient's genotype, especially the CC genotype, by 21.98-57.89% (p≤0.029-0.001), against the background of a decrease in the index of nonspecific reactivity and the ratio of agranulocytes to ESR – by 23.0 (p=0.039) and 15.74% (p=0.044), indicating the onset of specific immunological reactions in the active infectious process. Carriers of the mutational A-allele of the FGB gene (rs1800790) and the TT genotype of the TMPRSS2 gene (rs12329760) showed higher immune reactivity and resistance, which was significantly confirmed by the level of increase in immune reactivity by 6.31-17.21% (p=0.007) and 22.05-35.78% (p≤0.06-0.004), respectively, against the background of a slightly higher rate of allergy (especially in owners of the AG genotype of the FGB gene – by 68.18%, PAG=0.017), a higher ratio of agranulocytes and ESR – by 18.30-21.84% (p≤0.008-0.007) and 19.46-31.07% (p=0.023), with a higher ratio of lymphocytes and eosinophils – by 13.35-19.20% (p≤0.002-0.001). The influence of the wild-type T-allele of the eNOS gene (rs2070744), the A-allele of the FGB gene (rs1800790) and the TT genotype of the TMPRSS2 gene (rs12329760) on the immunological reactivity of the body of a patient with coronavirus infection was revealed.